A Digital Educational Game to Promote Inclusive Programming Education for Refugee Girls - Silva, Alexya; Laredo, Ana Clara; Valle, Pedro Henrique; Oliveira, Alessandreia (Anais do Women in Information Technology (WIT); 2026: Anais do XX Women in Information TechnologyDO - 10.5753/wit.2026.22156, 2026)
Digital Educational Games (DEGs) have been widely used to support teaching in several areas, especially in contexts that require inclusion and engagement. This work presents a DEG to introduce programming concepts to refugee girls aged 12–14, fostering interest in Computing and promoting gender equality. The tool incorporates accessible language, culturally representative narrative, and puzzle-based challenges aligned with programming concepts. We conducted a heuristic evaluation and a cognitive walkthrough, and the results identified usability issues and highlighted aspects related to engagement, representativeness, and educational potential. The DEG contributes to Sustainable Development Goals by promoting digital inclusion and empowering women.